WOMEN PARTICIPATION INTO THE AGITATIONAL POLITICS: A CASE STUDY OF LAHORE AND PESHAWAR - Kanval, Mamoona; Kulsoom, Dr. Ruqia; Dr. Gull-i-Hina (Journal of Arts & Social Sciences, 2022)
Freedom Movement had been explored by many scholars since independence from multiple dimensions. The role of women into freedom movement remained less explored due to focus on overall all India politics. The purpose of study is to explore detailed role of the Muslim women in civil disobedience movement of 1946 and their contribution in strengthening demand for Pakistan. the study is qualitative which is based on archival sources to get first hand information about the topic. The research reveals active participation of women in civil disobedience in Punjab and NWFP which was far ahead of their time. They came out of seclusion and participated in agitation and even offered arrests. Their participation built and enhanced pressure over the then provincial governments. Key words: Civil disobedience, Women politics, Punjab, NWFP